rDNA-ITS2 characterization of Trichogramma species (Hymenoptera: Trichogrammatidae) in Turkey - Fahriye Sümer Ercan; Mevlüde Alev Ateş; Sevcan Öztemiz (Egyptian Journal of Biological Pest Control, 2022)
Abstract Background ITS2 sequences can be used in systematic studies and proved to give reliable results in the distinguishing of Trichogramma species (Hymenoptera: Trichogrammatidae). Correct identification of natural enemies forms the basis of a biological control program. The present study aimed to compare sequences of rDNA-ITS2 of Trichogramma samples with those deposited in GenBank by using ITS2, as a barcode for reliable species identification and assessment of genetic diversity. Results Molecular identification methods were used to differentiate 2 Trichogramma species collected from Adana province of Turkey; Trichogramma brassicae (Bezdenko) and Trichogramma turkestanica Meyer (Hymenoptera: Trichogrammatidae). ITS2 sequences of samples ranged in size from 378 to 406 bp. The ITS2 sequences were aligned using Clustal W, genetic distances and phylogenetic tree were calculated using MEGA V7.0. rDNA-ITS2 sequences of 37 specimens of Trichogramma confirmed in GenBank in the study. Also, secondary structures of ITS2 sequences were predicted with the help of Mfold web server. All secondary structure constructions were performed at 37 °C using RNA version 2.3 default parameters. Conclusions A molecular marker can be used successfully to distinguish closely related groups if it is a rapidly evolving and highly conserved gene region. In the study, it was shown that ITS2 was a reliable molecular marker in distinguishing species. Therefore, with rDNA-ITS2 sequence analysis, Trichogramma spp., which is a very important natural enemy in biological control, has been identified.